A partially stripped massive star in a Be binary at low metallicity: a missing link towards Be X-ray binaries and double neutron star mergers - Ramachandran, Varsha; Klencki, J.; Sander, Andreas A. C.; Pauli, D.; Shenar, T.; Oskinova, Lidia M.; Hamann, W.-R. (Astronomy and astrophysics, 2023)
Standard binary evolutionary models predict a significant population of core helium-burning stars that lost their hydrogen-rich envelope after mass transfer via Roche-lobe overflow. However, there is a scarcity of observations of such stripped stars in the intermediate-mass regime (∼1.5 − 8 M⊙), which are thought to be prominent progenitors of SN Ib/c. Especially at low metallicity, a significant fraction of these stars are expected to be only partially stripped, retaining a significant amount of hydrogen on their surfaces. For the first time, we discovered a partially stripped massive star in a binary with a Be-type companion located in the Small Magellanic Cloud (SMC) using a detailed spectroscopic analysis. The stripped-star nature of the primary is revealed by the extreme CNO abundance pattern and very high luminosity-to-mass ratio, which suggest that the primary is likely shell-hydrogen burning. Our target SMCSGS-FS 69 is the most luminous and most massive system among the known stripped star + Be binaries, with Mstripped ∼ 3 M⊙ and MBe ∼ 17 M⊙. Binary evolutionary tracks suggest an initial mass of Mini ≳ 12 M⊙ for the stripped star and predict it to be in a transition phase towards a hot compact He star, which will eventually produce a stripped-envelope supernova. Our target marks the first representative of an as-yet-missing evolutionary stage in the formation pathway of Be X-ray binaries and double neutron star mergers.
Gesehen am 25.10.2023